Conducted Electromagnetic Susceptibility Analysis of Chips Based on BCI Method - Wen, Zheng; Wai Yie, Leong (INTI International University, 2025)
The bulk current injection (BCI) technique can simulate electromagnetic interference in the environment coupled with the power or signal cables of electronic devices. It is an important method for studying the conducted electromagnetic susceptibility in electromagnetic compatibility. This paper focuses on the conducted electromagnetic susceptibility of chips using the bulk current injection technique. The bulk current injection probe is integrated with various types of interference signals to design a conducted electromagnetic susceptibility test for chips based on multi-waveform interference. According to the results of the conducted electromagnetic susceptibility test, the susceptibility of integrated circuits to different types of interference signals is analyzed. The effectiveness of the test system is verified through experimental testing and data analysis. The research results show that the bulk current injection test method can accurately assess the conducted electromagnetic susceptibility of chips. It provides valuable references for the design optimization of electronic systems and the improvement of electromagnetic compatibility. This study contributes to improving the reliability of chips in complex electromagnetic environments